2009
DOI: 10.1002/pro.260
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of YnjE from Escherichia coli, a sulfurtransferase with three rhodanese domains

Abstract: Rhodaneses/sulfurtransferases are ubiquitous enzymes that catalyze the transfer of sulfane sulfur from a donor molecule to a thiophilic acceptor via an active site cysteine that is modified to a persulfide during the reaction. Here, we present the first crystal structure of a triple-domain rhodanese-like protein, namely YnjE from Escherichia coli, in two states where its active site cysteine is either unmodified or present as a persulfide. Compared to well-characterized tandem domain rhodaneses, which are comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 39 publications
(49 reference statements)
2
34
0
Order By: Relevance
“…Thus, we searched for proteins having the C-(X) 4 -R consensus and found that rhodaneses (sulfurtransferases) have highly conserved active-site loops with a CRXGX(R/T) motif (47). Surprisingly, the superposition of the Blh DUF442 with the catalytic domain of E. coli rhodanese YnjE (21) shows that the two domains have a similar fold and a remarkable conservation of the active-site residues, including the catalytic cysteine (supplemental Fig. S4), suggesting that DUF442 could display a rhodanese-like activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we searched for proteins having the C-(X) 4 -R consensus and found that rhodaneses (sulfurtransferases) have highly conserved active-site loops with a CRXGX(R/T) motif (47). Surprisingly, the superposition of the Blh DUF442 with the catalytic domain of E. coli rhodanese YnjE (21) shows that the two domains have a similar fold and a remarkable conservation of the active-site residues, including the catalytic cysteine (supplemental Fig. S4), suggesting that DUF442 could display a rhodanese-like activity.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, although alternating cycles of model building using COOT (12) and refinement with REFMAC5 (13) allowed the modeling of 96 out of the 102 residues expected in the asymmetric unit (a single monomer), R work /R free values remained at 0.230/0.263, and the addition of water molecules caused the R free to rise. Refinement was done against both native and derivative data processed in the space group P3 1 21, and the same problem was encountered. At this point, lower symmetry space groups were applied, and structure refinement could only be accomplished in P1.…”
Section: Methodsmentioning
confidence: 99%
“…The enzymatic reaction takes place in two steps. In the first step, the thiol group of the cysteine reacts with the thiosulfate anion (S 2 O 3 Ϫ ) to form an enzyme-persulfide intermediate, which reacts in a second step with the cyanide ion to produce thiocyanate (SCN Ϫ ) (7)(8)(9). Although the crystal structure of the sulfur-free and the persulfide form of one member of the rhodanese family (GlpE) as well as the solution state NMR structure of another member (PspE) have been determined (3,4,10), the molecular mechanism of the sulfurtransferase activity remains unclear (11), but the dynamics appear to be involved (3).…”
mentioning
confidence: 99%
“…In each case, only the C-terminal domain contains the catalytic cysteine residue. The crystal structure of YnjE has been solved recently (19). YnjE can efficiently be persulfurated by IscS while having only a residual activity with thiosulfate as substrate (19).…”
mentioning
confidence: 99%
“…The crystal structure of YnjE has been solved recently (19). YnjE can efficiently be persulfurated by IscS while having only a residual activity with thiosulfate as substrate (19). The role of YnjE so far remained enigmatic for E. coli.…”
mentioning
confidence: 99%